THE USE OF E-LEARNING AS LEARNING MEDIUM AT SECONDARY VOCATIONAL SCHOOL - Candra Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
In addition to conventional learning in the form of face to face in the classroom, the use of information technology can also support the learning system where it is possible to do without face to face learning. One of learning that is currently widely used is electronic learning or E-Learning. In this activity carried out the installation of E-Learning, training of the use for administrators and teachers, and monitoring the use of these media in learning activities. Based on the results of training can be seen that the E-Learning media is quite attractive and easy to operate. But some teachers are still experiencing difficulties. Complexity feature is often felt by those who first used this medium. But in general, participants also stated that this application is very useful for learning. From the results of monitoring can also be known that the facilities are quite helpful is the online exam application. This application can be used primarily to prepare students to face the online final exam. It can thus be concluded that the activities undertaken to provide benefits or impact on improving the performance learning activities at Secondary High School. However, still need to hold advanced training to enhance the understanding of E-Learning application.